Local welfare systems in Europe and the economic crisis. (July 2016) - Andreotti, Alberta; Mingione, Enzo
The tendency towards the diffusion of more localised welfare provision is part of the wider post-industrial transformation and challenges the citizenship protection system that developed during the Fordist age. It is assumed that local welfare provision is more efficient and less expensive than centralised national welfare programmes. In this article we argue first that the process of transformation and localisation of welfare is driven by two different (sometimes opposing) forces: (1) the necessity to identify effective ways of responding to the need for social support which is increasingly individualised, fragmented and heterogeneous, and therefore to expand 'active' social policies; and (2) the necessity to keep under control (and more often reducing) national public spending. Second, we argue that a more integrated welfare system (involving the third sector, voluntary organisations and private providers) and one which is more locally differentiated poses a series of problems in terms of social and territorial inequalities. We then identify some conditions that can help to keep inequalities under control. In the conclusion we will see how the crisis is exacerbating these tendencies.